Electrospun patches to deliver combination drug therapy for fungal infections - Dziemidowicz, Karolina; Meszarik, Mark; Piovesan, Jacopo; Almatroudi, Mazna A.; Williams, Gareth R.; Murdan, Sudaxshina (Frontiers in Drug Delivery, 2024)
Fungal infections, though affecting healthcare globally, receive insufficient attention in clinical and academic settings. Invasive fungal infections, particularly caused by combat wounds, have been identified as a critical threat by the US Department of Defense. Monotherapy with traditional antifungals is often insufficient, and so combination therapies are explored to enhance treatment efficacy. However, systemic combination treatments can result in severe adverse effects, suggesting the need for localised delivery systems, such as drug-loaded electrospun patches, to administer antifungals directly to the infection site.This proof-of-concept study hypothesised that dual amorolfine and terbinafine therapy slowly releasing from electrospun patches would be an effective way of eradicating Candida albicans when the patch was applied directly to the fungal colony. The feasibility of creating electrospun materials loaded with amorolfine and terbinafine for combination antifungal therapy was investigated. Electrospinning was used to fabricate polycaprolactone (PCL) patches with varying drug loadings (2.5%, 5%, and 10% w/w) of amorolfine and terbinafine either individually or in combination. The incorporation of both drugs in the fibres was confirmed, with the drugs predominantly in an amorphous state. Results showed that combination therapy patches had a significantly greater and prolonged antifungal effect compared to monotherapy patches, with larger zones of inhibition and sustained efficacy over at least 7 days. This study therefore demonstrates that PCL-based electrospun patches containing amorolfine and terbinafine provide superior antifungal activity against Candida albicans compared to monotherapy patches. This approach could enhance patient compliance due to prolonged drug release, leading to more effective antifungal therapy.